2022
DOI: 10.1101/2022.11.30.22282833
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High SARS-CoV-2 seroprevalence in Lagos, Nigeria with robust antibody and cellular responses

Abstract: Background Early evidence suggested that the impact of the COVID-19 pandemic was less severe in Africa compared to other parts of the world. However, more recent studies indicate higher SARS-CoV-2 infection and COVID-19 mortality rates on the continent than previously documented. Research is needed to better understand SARS-CoV-2 seroprevalence and immunity in Africa. Methods Our collaboration with the Lagos State COVID-19 Taskforce, enabled secondary analyses of immune responses in healthcare workers (HCWs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…In early 2021, we studied the immune responses in Nigerian healthcare workers (HCWs) at Lagos University Teaching Hospital (n=134) and in Oxford/AstraZeneca COVID-19 vaccine recipients from the general population (n=116) across five local government areas (LGAs) in Lagos state. 5 Antibodies directed to only SARS-CoV-2 N in the absence of S antibody reactivity were detected in 9.7% (13/134) of HCWs and 15.5% (18/116) of the general population. This antibody profile directed to the SARS-CoV-2 N alone was suggestive of pre-existing cross-reactive immunity stemming from prior hCoV infection.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In early 2021, we studied the immune responses in Nigerian healthcare workers (HCWs) at Lagos University Teaching Hospital (n=134) and in Oxford/AstraZeneca COVID-19 vaccine recipients from the general population (n=116) across five local government areas (LGAs) in Lagos state. 5 Antibodies directed to only SARS-CoV-2 N in the absence of S antibody reactivity were detected in 9.7% (13/134) of HCWs and 15.5% (18/116) of the general population. This antibody profile directed to the SARS-CoV-2 N alone was suggestive of pre-existing cross-reactive immunity stemming from prior hCoV infection.…”
Section: Discussionmentioning
confidence: 95%
“…1-2). 5,26 In one of the few studies conducted on samples from Africa prior to the COVID-19 pandemic, Tso et al reported higher reactivity to hCoV N and S antigens with significantly higher rates of cross-reactivity in Zambia (14.1%) and Tanzania (19%) compared to the US (2.4%). 27 In a multi-national study, Pedersen et al reported higher SARS-CoV-2 N reactivity in Gabon (20/116,17.2%) compared to reactivity in Canada, Denmark, and Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, studies in the DRC have found seroprevalences ranging from 48% 12 to 70% 13,14 . A similar phenomenon has occurred in neighboring countries such as Republic of the Congo, 15 Cameroon, 16 Gambia, 17 Somalia, 18 Uganda, 12,14,19 Tanzania, 20 Nigeria 12,21,22 and Kenya, 23–25 where growing evidence indicates pandemic burden has been grossly underestimated.…”
Section: Introductionmentioning
confidence: 93%